ANALISA PENGARUH MANAJEMEN LABA DAN ASIMETRI INFORMASI TERHADAP COST OF EQUITY CAPITAL (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013) - Adi Baskara Perwira; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to examine and provide analysis related to the effect of the relationship Profit Management and Information Asymmetry of the Cost of Equity Capital.hipotesis proposed (1) the information asymmetry positive and significant impact on the cost of equity capital, (2) Management profit positive and significant impact on costs equity capital. The population in this study are manufacturing companies listed on the Stock Exchange 2010-2013. Data were collected using purposive sampling method of the companies listed in the Indonesia Stock Exchange. Descriptive statistical analysis used in this study to provide a picture or description, the maximum value, minimum value, average value (mean) and standard deviation to the asymmetry of information, management of earnings and cost of equity capital. Results of the study found that the information asymmetry positive and significant impact on the cost of equity capital. These results show that the greater the value of asymmetry of information will increase the cost of equity capital. While profit management no significant effect on the cost of equity capital. These results indicate that the size of the earnings management behavior does not determine the increase in the cost of equity capital.